2021
DOI: 10.20377/jfr-474
|View full text |Cite
|
Sign up to set email alerts
|

Gendered integration? How recently arrived male and female refugees fare on the German labour market

Abstract: Objective: This paper examines gender differences in the labour market integration of newly arrived refugees in Germany. In particular, we focus on the heterogeneity in employment rates among female refugees. Background: Previous research has demonstrated that refugee women are disadvantaged on the labour market not only compared to their male counterparts, but also compared to other immigrant women. So far, however, little is known about the mechanisms that underlie the specific disadvantages of refugee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Migration scholars contend that the labor market integration of female refugees falls far behind that of their male counterparts (Pittaway and Bartolomei, 2001;Dumper, 2002;Koyama, 2015;Cheung and Phillimore, 2017;Salikutluk and Menke, 2021;Kosyakova et al, 2022a). In this context, the term "triple disadvantage" emerged, suggesting a cumulative disadvantage related to immigration, refugee status and gender (Liebig and Tronstad, 2018) .…”
Section: Refugees' Labor Market Situationmentioning
confidence: 99%
See 2 more Smart Citations
“…Migration scholars contend that the labor market integration of female refugees falls far behind that of their male counterparts (Pittaway and Bartolomei, 2001;Dumper, 2002;Koyama, 2015;Cheung and Phillimore, 2017;Salikutluk and Menke, 2021;Kosyakova et al, 2022a). In this context, the term "triple disadvantage" emerged, suggesting a cumulative disadvantage related to immigration, refugee status and gender (Liebig and Tronstad, 2018) .…”
Section: Refugees' Labor Market Situationmentioning
confidence: 99%
“…female refugees' labor market disadvantage decreases but never fully vanishes (Bakker et al, 2017;Brell et al, 2020;Kanas and Steinmetz, 2021;Salikutluk and Menke, 2021;Kosyakova et al, 2022a).…”
Section: Refugees' Labor Market Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have also observed that refugee women face a double disadvantage, as their employment rate falls significantly below that of refugee men, of other migrant men and women and of the majority population (Brücker et al, 2019;Brücker, Kosyakova, & Vallizadeh, 2020;Elwood Carlson & Williams, 2020;Graeber & Schikora, 2020;Kosyakova & Brenzel, 2020;Liebig & Tronstad, 2018;Maliepaard et al, 2017;Salikutluk & Menke, 2021;Spörlein et al, 2020;Worbs & Baraulina, 2017). For example, five years after their arrival in Germany, 29% of Syrian female refugees were employed, as compared with 57% of Syrian male refugees (Brücker, Kosyakova, & Schuß, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…In this time frame, the gaps between employment rates of refugees and other migrants range from one percent point in the US over 45 percent points in Germany to 69 percent points in Norway (Brell et al, 2020). Generally, refugee women's labour market integration happens more slowly than that of men (Tervola, 2020)-in Germany, the gap between male and female refugees' labour market participation is 29 percentage points (Brücker et al, 2020), and this trend is also observed in other OECD countries (Salikutluk & Menke, 2021). However, studies have shown that achieving employment is as much an integration goal for recently arrived refugee women as it is for their male counterparts (Liebig & Tronstad, 2018).…”
mentioning
confidence: 95%